Ascocerid cephalopods from the Hirnantian?-Llandovery stages of the southern Paraná Basin (Paraguay, South America): First record from high paleolatitudes - Cichowolski, Marcela (2018)
Ascocerid cephalopods are described for the first time from high paleolatitudes of Gondwana. Studied material was collected from the Hirnantian?-Llandovery strata of the Eusebio Ayala and Vargas Pena formations, Parana Basin, southeastern Paraguay. The specimens are poorly preserved and were questionably assigned to the subfamily Probillingsitinae Flower, 1941, being undetermined at genus and species rank because diagnostic characters are not visible. A particular feature seen in our material is the presence of both parts of the ascocerid conch (the juvenile or cyrtocone and the mature or brevicone) joined together, which is a very rare condition in the known paleontological record. The specimens are interpreted as at a subadult stage of development because fully grown ascocerids would have lost the juvenile shell. A planktonic vertical migrant mode of life with a subvertical attitude is proposed for the juvenile, and a horizontal demersal nektonic mode for the adult form, as has been previously suggested. A subvertical orientation near the bottom is proposed for the subadult stage. We suggest that the immigration of ascocerids to southwestern Gondwana was possible through ocean currents that would carry the planktonic juveniles from low to high latitudes during the end-Ordovician postglacial transgression that flooded the intracratonic basins of the region.